The Role of Citizen Journalism in Democratic Discourse - Demsy Wattimena (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This study examines the evolving role of citizen journalism in contemporary democratic discourse, analyzing how digital technologies have transformed traditional media landscapes and enabled new forms of civic participation. Through a comprehensive review of international literature and empirical analysis, this research investigates the democratic implications of citizen journalism as both a complement to and challenge for professional journalism. The findings reveal that while citizen journalism enhances democratic participation by providing diverse perspectives and facilitating community engagement, it also presents challenges related to information credibility, ethical standards, and potential polarization. The study concludes that citizen journalism serves as a crucial component of democratic discourse when properly integrated with professional journalism standards and supported by appropriate regulatory frameworks.